Acoustic topological devices based on emulating and multiplexing of pseudospin and valley indices - Meng Gao; Shiqiao Wu; Jun Mei (New Journal of Physics, 2020)
We present a design paradigm for acoustic devices in which robust and controllable transport of wave signals can be realized. These devices are based on a simple acoustic platform, where different topological phases such as acoustic quantum spin Hall and quantum valley Hall insulators are emulated by engineering the spatial symmetries of the structure. Edge states along interfaces between different topological phases are shown to be promising information channels, where the multiplexing of pseudospin and/or valley degrees of freedom is unambiguously demonstrated in various devices including a multiport valve for acoustic power dividing and feeding. The information capacity in the input channel is substantially enhanced due to the creating of an extra dimension for the data carriers. The topological devices proposed here, when integrated with other state-of-the-art communication techniques, may suggest a significant step towards acoustic communication circuits with complex functionalities.